If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 + -6x = -28 Solving -10 + -6x = -28 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -6x = -28 + 10 Combine like terms: -10 + 10 = 0 0 + -6x = -28 + 10 -6x = -28 + 10 Combine like terms: -28 + 10 = -18 -6x = -18 Divide each side by '-6'. x = 3 Simplifying x = 3
| -8+6x-3x=-26 | | 1/5(3x+4)-3/8(5-2x)=5(2x-7) | | -1-6(-b-4)=8b+7 | | h+12-5h=28 | | (x)-7=50 | | 3+2n+3n=10+6n | | (4/7y)^2 | | 4*0=5*0 | | 5/3p=-40 | | 9-(-3V-9)=54 | | 45=10x+15 | | 2(y+3)=3y+7 | | n-7=3-4n | | X=10-1/3y | | 5(3+7x)=-2x+15 | | 69(2x+4)=180 | | 10z-4+(k+11)=8k-7 | | T+12.7=-7.4 | | 15g-14g=16 | | 14x+4y+20+16x-5y-18= | | 9-(3V-9)=54 | | 142(2x+4)=180 | | -175=-7(5x-30) | | V-1=1+2v | | 7.61=2(3.14r) | | w/102=102 | | (x)=12 | | n+(n+2)=97 | | 32(2x+4)=180 | | 12-4x=-18+4x | | x^2+12x=c | | -0.75x+5=0.25x-3 |